U.S. Hispanic Catholics in the pews. Issue 4 (2nd October 2018) - Gray, Mark
Abstract: In recent decades, Hispanics have been the fastest growing segment of the U.S. Catholic population. The Center for Applied Research in the Apostolate has documented the demography of this population, where Hispanics worship, and how they evaluate their parish. This article provides a twenty-first century portrait of the Catholic Church through the lens of Hispanic parishioners. It documents the broad embrace of multiculturalism among Hispanic Catholics and the growing numbers of Hispanics preparing for new roles in parish ministry and leadership.